2011
DOI: 10.1007/s11746-011-1889-6
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging Activity and Performance of Novel Phenolic Antioxidants in Oils During Storage and Frying

Abstract: Novel phenolic antioxidants: 2a (6 0 -hydroxy-2 0 , 5 0 ,7 0 ,8 0 -tetramethylchroman-2 0 -yl)methyl 3-methoxy-4-hydroxycinnamate, 2b (6 0 -hydroxy-2 0 ,5 0 ,7 0 ,8 0 -tetramethylchroman-2 0 -yl)methyl 3,5-dimethoxy-4-hydroxycinnamate, 2c (6 0 -hydroxy-2 0 ,5 0 ,7 0 ,8 0 -tetramethylchroman-2 0 -yl)methyl 3,4-dihydroxycinnamate, and 3 (6-hydroxy-2,5,7,8-tetramethylchroman-2-yl)methyl (6 0 -hydroxy-2 0 ,5 0 ,7 0 ,8 0 -tetramethylchroman-2 0 -carboxylate) have been prepared in good yields and fully characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The antioxidant activity determined was 3.00 ± 0.30 μM Trolox equivalents/μM caffeic acid. This value is within the range of results obtained in previous studies. …”
Section: Resultssupporting
confidence: 89%
“…The antioxidant activity determined was 3.00 ± 0.30 μM Trolox equivalents/μM caffeic acid. This value is within the range of results obtained in previous studies. …”
Section: Resultssupporting
confidence: 89%
“…The key goal of this study was to determine if new lipid antioxidants exert any detrimental effects on human cells and tissues. In the present studies, we focused on four of the recently reported novel antioxidants: trolox trihydroxybenzoate (1a) 12 ; trolox 3,5-dimethoxy-4-hydroxycinnamate (1b) 13 ; and derivatives of dihydrocaffeic acid amide, (2a) and (2b) 10 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Samples are heated at 185 ± 5°C with mixing for 2 h. The validity of the test was assessed by analysis of total polar compounds and of the amounts of residual tocopherols and comparison of results with those obtained in assays on commercial fryers . The method has been later applied to assess the activity of novel phenolic antioxidants prepared from Trolox under frying conditions .…”
Section: Evaluation Of Antioxidant Efficacy In Fryingmentioning
confidence: 99%